A STUDY OF EXPERIENTIAL ARCHEOLOGY OF A POEM BY FERNANDO PESSOA - Motaianu, Mihaela (Design/Arts/Culture, 2022)
This paper describes an experiential archaeology project carried out in three cities in Portugal, Mação, Tomar and Lisbon and analyses, from a poetic perspective, the effects of Time on matter using psychogeography as a method of exploring the urban landscape. In this case psychogeography was used to experience a poem by the great Portuguese modernist writer and poet Fernando Pessoa, in the same way an observer experiences a cityscape. Photographs of ruins that show traces of degradation caused by the passage of time are presented in the form of four condensed visual narratives that visualise four different versions of the poem’s verses.